BiRch:a bidirectional search algorithm for k-step reachability queries - Jun-feng ZHOU; Wei CHEN; Chun-ping FEI; Zi-yang CHEN (Tongxin xuebao)
A new bidirectional processing algorithm,namely BiRch was proposed.When checking whether a vertex u can reach v within k steps,BiRch firstly compared the out-degree of u and the in-degree of v,and processed the one with smaller degree,such that to avoid large indexes and the inefficiency due to large degree.Two pruning strategies were proposed based on bidirectional breadth-first levels and bidirectional topological levels,such that to reduce the number of visited vertexes.Experimental results on 19 real datasets verify the efficiency of the proposed method in terms of different metrics,including indexing time,index size,query processing time,the number of visited vertexes,and scalability.